Image 4_COVID-19 mitigates the response to TKIs in patients with CML via the inhibition of T-cell immunity.pdf - Na He (295300) (2024)
Introduction Chronic myeloid leukemia (CML) is a severe hematological malignancy characterized by BCR-ABL fusion gene. The advent of tyrosine kinase inhibitors (TKIs) targeting BCR-ABL has improved the landscape of CML treatment dramatically. The occurrence of coronavirus disease 2019 (COVID-19) has challenged many cancers. However, its effect on TKI therapy of CML remains unknown. Methods In this study, we collected peripheral blood from chronic phase CML patients treated with TKIs at low-level BCR-ABL P210 during COVID-19 pandemic, and determined the alterations of BCR-ABL P210 by applying the well-established BCR-ABL P210 detection system. Results Our results showed that the level of BCR-ABL P210 of CML patients was significantly elevated shortly after contracting COVID-19, and then recovered to pre-infection level within one month. The elevated degree of P210 was positively correlated with the duration of COVID-19. And the level of P210 was elevated in CML patients that took COVID-19 vaccination. Furthermore, lymphocyte subsets and cytokine detections were performed by flow cytometry to analyze the alteration of immune responses. Our results showed that effector CD8+ T (Teff) cells were significantly downregulated while naïve CD8+ T cells or Treg cells were obviously upregulated in P210-elevated CML patients after contracting COVID-19 compared to that in P210-unchanged or decreased CML patients. Moreover, the SARS-CoV-2 pseudovirus was constructed to further determine its effects. The results showed that the level of BCR-ABL P210 was upregulated upon transfection of SARS-CoV-2 pseudovirus into blood samples of CML patients. Discussion Our results demonstrate that COVID-19 suppresses the immune activity and consequentially elevates the level of BCR-ABL P210 of CML patients.